Information and Communication Technologies for Health Systems Strengthening : Opportunities, Criteria for Success, and Innovation for Africa and Beyond - Otto, Kate; Shekar, Meera; Herbst, Christopher H.; Mohammed, Rianna (World Bank, Washington, DC, 2015)
Information and communication technologies (ICT) for health or eHealth solutions hold great potential for generating systemic efficiencies by strengthening five critical pillars of a health system: human resources for health, supply chain management, health care financing, governance and service delivery, and infrastructure. This report describes the changing landscape of eHealth initiatives through these five pillars, with a geographic focus on Sub-Saharan Africa. This report further details seven criteria, or prerequisites, that must be considered and addressed in order to effectively establish and scale up ICT-based solutions in the health sector. These criteria include infrastructure, data and interoperability standards, local capacity, policy and regulatory environments, an appropriate business model, alignment of partnerships and priorities, and monitoring and evaluation. In order to bring specific examples of these criteria to light, this report concludes with 12 specific case studies of potentially scalable ICT-based health care solutions currently being implemented across the globe at community, national, and regional levels. This report is intended to be used by development practitioners, including task team leaders at the World Bank, to strengthen their understanding of the use of ICT to support health systems strengthening (HSS) efforts as well as to highlight critical prerequisites needed to optimize the benefits of ICT for health.